(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the differences observed between the original 1914 publication and subsequent reprints of Chulpon’s story “Doctor Muhammadiyor,” a representative work of Jadid literature.